Acquisition of English Vowel Sounds at Nursery Level: An Empirical Study Based on the Application of Gamification Strategy - Muhammad Ali Shahid; Anser Mahmood; Ali Furqan Syed (Linguistics and Literature Review, 2022)
The current empirical study aimed to stimulate and measure the competence level of children for learning vowel sounds at nursery level at Right School, Model Town, Sillanwali. Sound-bingo strategy was used for distinguishing and learning vowel sounds in the context of gamification efficacy. Gamification frameworks can boost dedication, while also developing learning execution at the same time. In any case, only a few studies have been undertaken to address the constructs used to analyse the effects of gamification on people. The current study implemented Mathew Nudds and Casey Callaghan’s ‘Theory of Auditory Perception’ as its theoretical framework. According to the theory, the information we hear is comprehensible. The researchers used the purposive sampling technique and an achievement test to obtain data for this study. Data was collected from two distinct groups of twenty-five students apiece, named Iqbal and Quaid, respectively. Quaid group was designated as the control group and Iqbal group as the experimental group. Utilising the gamification technique, both groups were subjected to a test without learning. Sound-bingo technique was utilised to deliver a specific corpus of vowel sounds to Iqbal group. The results revealed that when an activity is gamified, a meaningful goal needs to be provided before the action can be adequately rated. An all around organised game could help to enhance children’s motivation, commitment, and mental turn of events. The current study concludes that gamification can influence the students’ attitudes toward language learning and its effective application can help them learn better.Keywords: achievement test, English vowel sounds, gamification,  interest, nursery class, sound-bingo technique